Diabetic Retinopathy Department - Sari, Citra Belia Candra; Wardhani, Gustri Kusuma; Haryono, Tri Agus (Jurnal Indonesia Sosial Sains, 2025)
Diabetic retinopathy (RD) is one of the chronic microvascular complications of diabetes mellitus which is the leading cause of preventable blindness worldwide. This condition arises as a result of chronic hyperglycemia that triggers oxidative stress, inflammation, and retinal endothelial dysfunction, resulting in capillary leakage, microvascular occlusion, and pathological neovascularization. This study aims to provide a comprehensive understanding of pathophysiological aspects, epidemiology, classification, clinical manifestations, diagnosis, management, and prevention strategies for Diabetic Retinopathy, emphasizing the relationship between the control of systemic risk factors and disease progressivity. This study uses a literature review-based descriptive approach by analyzing secondary data from various scientific publications, clinical guidelines, and global health reports, including from WHO, ADA, and the Indonesian Ministry of Health. The results of the study show that the prevalence of RD is increasing along with the increase in the number of diabetics globally and nationally. Major risk factors include poor glycemic control, hypertension, dyslipidemia, and long duration of diabetes. Early detection through wide pupil funduscopy as well as therapies such as laser photocoagulation and anti-VEGF injections have been shown to be effective in slowing the progression of the disease. RD is a complex disease that requires a multidisciplinary approach to diagnosis and treatment. Optimal control of glucose levels and blood pressure as well as regular retinal examinations are essential to prevent permanent blindness. This study contributes to enriching the national literature related to diabetic ocular complications and provides recommendations for strengthening routine screening, patient education, and further research on innovative therapies based on biomarkers and anti-VEGF agents to improve vision quality and reduce the rate of blindness due to RD.